Remdesivir and molnupiravir had comparable efficacy in lung transplant recipients with mild-to-moderate COVID-19: a single center experience - Razia, Deepika; Sindu, Devika; Cherrier, Lauren; Grief, Katherine; Walia, Rajat; Tokman, Sofya (Frontiers in Transplantation, 2024)
Remdesivir (REM) and molnupiravir (MOL) are commonly used to treat LTRs with COVID-19; however, the clinical efficacy of these medications is yet to be compared. In this retrospective cohort study, we compared the clinical outcomes between LTRs with mild-to-moderate COVID-19 treated with REM and those treated with MOL. Between March 2020 and August 2022, 195 LTRs developed COVID-19 at our center. After excluding 82 who presented with severe disease requiring hospitalization, the remaining 113 were included in the analysis: 54 did not receive antiviral treatment, 30 were treated with REM, and 29 were treated with MOL. Adjusted multivariable logistic regression analysis showed similar rates of hospitalization (adjusted odds ratio (aOR) 1.169, (95% confidence interval (95%CI) 0.105 - 12.997, p=0.899), ICU admission (aOR 0.822, 95%CI 0.042 - 16.220, p=0.898), mechanical ventilation (aOR 0.903, 95%CI 0.015 - 55.124, p=0.961), and COVID-19-related mortality (aOR 0.822, 95%CI 0.042 - 16.220, p=0.898) between LTRs treated with REM and those treated with MOL for mild-to-moderate COVID-19, irrespective of SARS-CoV-2 strain. MOL may be a suitable alternative to REM to treat LTRs with mild-to-moderate COVID-19, and the choice of antiviral therapy can be driven by practical considerations such as route of administration and drug availability.